Observation of yttrium oxide nanoparticles in cabbage (Brassica oleracea) through dual energy K-edge subtraction imaging. Issue 1 (December 2016) - Chen, Yunyun; Sanchez, Carlos; Yue, Yuan; Almeida, Mauricio; González, Jorge; Parkinson, Dilworth; Liang, Hong
Abstract Background The potential transfer of engineered nanoparticles (ENPs) from plants into the food chain has raised widespread concerns. In order to investigate the effects of ENPs on plants, young cabbage plants (Brassica oleracea ) were exposed to a hydroponic system containing yttrium oxide (yttria) ENPs. The objective of this study was to reveal the impacts of NPs on plants by using K-edge subtraction imaging technique. Results Using synchrotron dual-energy X-ray micro-tomography with K-edge subtraction technique, we studied the uptake, accumulation, distribution and concentration mapping of yttria ENPs in cabbage plants. It was found that yttria ENPs were uptaken by the cabbage roots but did not effectively transferred and mobilized through the cabbage stem and leaves. This could be due to the accumulation of yttria ENPs blocked at primary-lateral-root junction. Instead, non-yttria minerals were found in the xylem vessels of roots and stem. Conclusions Synchrotron dual-energy X-ray micro-tomography is an effective method to observe yttria NPs inside the cabbage plants in both whole body and microscale level. Furthermore, the blockage of a plant's roots by nanoparticles is likely the first and potentially fatal environmental effect of such type of nanoparticles.